THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON THE IMAGE OF COMPANIES DOING CSR IN KUNMING - Yang Ya; Suwattana Tungsawad; Sunanta Laohanan; Hathaikorn Pun-ngam; Komm Pechinthorn (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This paper takes the Kunming Company as an example to analyze the impact of corporate social responsibility on corporate image. In this study, corporate governance, quality of life of employees, responsibility to consumers, community and social development as the background of the research; Corporate social responsibility on the uniqueness of the company, products and services, corporate reputation, corporate interpersonal image is the focus of the analysis. The research data were collected from various groups of companies in Kunming by means of questionnaires. The results of this study show that while creating profits and assuming legal responsibilities to shareholders and employees, enterprises should also make contributions to the environment, consumers and society. At the same time, corporate social responsibility has a profound impact on all aspects of the corporate image, corporate social responsibility also affects the development prospects of a company.